Diseño y configuración de una infraestructura de red basado en el modelo de capas de CISCO, instancia de prueba con simulador de red, para el M. I. Municipio del cantón Chilla - Chamaidán Vega, Saida Jessenia (2010)
This project aims to perform and improve the daily activities of the Municipality, where ICT is involved, to do so will be designed and set up a network infrastructure based on Descending Methodology Network and the shell model CISCO, whose viability was demonstrated in network simulator, where the appropriate tests are performed.